Copper-catalyzed 1,2,2-trifunctionalization of maleimides with 1,7-enynes and oxime esters via radical relay/1,5-hydrogen-atom transfer - Jiang, Li-Lin; Qiu, Hui; Zhou, Yu; Wang, Ling-Tao; Yang, Wen-Hui; Deng, Chao; Wei, Wen-Ting (ORGANIC CHEMISTRY FRONTIERS, 2023)
The trifunctionalization of alkenes has emerged as a versatile strategy for the efficient construction of diverse structural units and complex molecules in synthetic chemistry. Herein, we describe a novel 1,2,2-trifunctionalization of maleimides with 1,7-enynes and oxime esters through simultaneous construction of four C-C bonds and a C=N bond in one pot based on the radical relay/1,5-hydrogen-atom transfer (HAT) processes under a mild copper catalytic system. The resulting reaction of spirocyclic derivatives displays high chemical selectivity, broad substrate scope, as well as high atom- and step-economy. Preliminary control experiments and density functional theory (DFT) calculations reveal sequential functionalizations and cyclizations in this transformation.